SISTEM PENDUKUNG KEPUTUSAN PROMOSI KENAIKAN JABATAN DENGAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) DI FINESTWOOD - Yogaswara Adam Rohimat; Dwi Yulistyanti; Purni Munah Hartuti (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2022)
One of the benefits of the application is to simplify and speed up existing business processes in the company or home industry, the data generated is also accurate. The author proposes to implement a Decision Support System application to assist and simplify existing business processes at Finestwood. With this application at Finestwood, it is hoped that it can help facilitate existing business processes so that they become faster and more accurate. The author uses preliminary research in Research and Development (RD). This study aims to collect information both in the form of problems and potentials that can be developed in research. Then the system development steps carried out by the author include analyzing the needs of the application, literature study, system design. starting with designing the database, from what tables are needed, the relations between the tables so that the resulting system is efficient. The design of the interface faces the convenience and ease of users in this application later. In making this application, the author uses several tools, including Microsoft SQL Server Management Studio for database design and Microsoft Visual Studio for application interface design. The author uses this second tool from Microsoft because most computer users use the Windows Operating System in their daily use.